The Effects of Elite Puroindoline Gene Alleles on the Kernel Hardness of Chinese Winter Wheat - Qinglin Wen; Shan Lu; Pengfang Qiao; Liang Chen; Yingang Hu (Agronomy)
Kernel hardness (KH) is a significant factor that influences wheat quality. In order to gain a better understanding of KH profiles and the effects of its associated genes in Chinese wheat cultivars growing under normal and latest stage drought stress conditions, 206 wheat cultivars were examined. The kernel hardness index (KHI) was measured by utilizing a single kernel hardness tester, and allelic variations of the puroindoline genes regulating KH were detected using KASP markers. The hardness test indicated that 121 (58.7%) were classified as hard wheat, 39 (18.9%) as soft wheat, and 46 (22.3%) as mixed wheat. Genotypic analysis revealed that 10 cultivars (4.9%) carried the superior Pina-D1b allele, 143 cultivars (69.4%) possessed the Pinb-D1b allele, representing the main allele for hard wheat, and 45 cultivars (21.8%) contained the Pinb-B2b allele. An analysis of the cumulative effect across five gene loci indicated that among the tested materials, none contained all five excellent gene loci simultaneously. However, materials with combinations of two, three, or four excellent gene loci exhibited significantly higher KHI values compared to those with zero or only one excellent locus. This finding suggests that the accumulation of excellent gene loci can enhance KH. Among various allelic combinations, Pina-D1 + M0159 displayed remarkably higher KH values than the others. Conversely, Pinb-D1 + M0380 exhibited significantly lower KH values. Drought stress during the late growth stage of wheat could enhance KH.